Pulmonary cryptococcosis with or without immunocompromise: a retrospective comparative study of clinical and CT features and influential factors for lesion absorption - Juan Liao; Wenzhao Zhang; Liqing Peng; Ying Liu; Dianying Liao; Jianqun Yu (Frontiers in Medicine, 2026)
Background Pulmonary cryptococcosis (PC) is an invasive fungal infection with rising incidence in immunocompetent populations. The differential clinical and imaging characteristics between immunocompromised (ICP) and non-immunocompromised (NICP) patients remain incompletely characterized, limiting precision in diagnosis and management. Method A retrospective study was conducted on 117 patients with confirmed PC from a single tertiary center. Patients were stratified into ICP and NICP groups based on refined criteria. Clinical symptoms, laboratory findings, and chest CT imaging features were systematically compared. Quantitative volumetric analysis was performed on follow-up CT scans ( n = 31) to calculate the degree of absorption (DOA). LASSO regression was used for exploratory prognostic factor analysis. Result A high proportion of patients (59.0%) were asymptomatic at presentation. After False Discovery Rate (FDR) correction, no significant differences in clinical symptoms were found between ICP and NICP groups. Laboratory profiles, however, provided objective differentiation, with ICP patients showing significantly lower red blood cell counts and albumin levels (all Q < 0.05). CT imaging revealed that solitary nodules (Type I) were more common in NICP patients (Q = 0.030), while complex patterns like patchy consolidation (Type III) and numerous lesions (≥10) were significantly associated with ICP status (Q = 0.035). The halo sign was not a robust differentiator after FDR correction (Q = 0.105). Serum CrAg testing showed high diagnostic accuracy (83.9% positivity). In follow-up, a significantly lower DOA was observed in ICP patients (75.1% vs. 86.7%, P = 0.038). The conservative LASSO model identified no robust predictors of DOA, but an exploratory analysis nominated imaging type, immune status, and treatment duration as candidate factors. Conclusions The clinical presentation of PC is non-specific and cannot reliably differentiate immune status, underscoring the necessity of integrated laboratory and radiographic evaluation. ICP patients present with distinct laboratory abnormalities and more complex imaging patterns. Treatment response assessment should combine clinical, radiographic, and serological trends, as antigen persistence is common. From a clinical perspective, population-based screening is not recommended given the high proportion of incidentally discovered cases; instead, diagnostic vigilance during routine imaging should be emphasized. In immunocompetent patients with small solitary lesions, surgery alone represents an effective option that can reduce the need for prolonged antifungal therapy. Larger prospective studies are needed to validate the exploratory prognostic factors identified.